Mary, Mother of God
1 online resource (468 pages)
Keywords: By clothing the Word with her flesh, the Virgin Mary made God visible, manifesting Christ as a perfect “image” of the Father. By virtue of this archetypal “artistry” of Incarnation, Mary mediates the tradition of Christian image-making. This volume explores images of the Mother of God in early modern devotion, piety, and power. The book is divided into four sections, the first three of which link the subjects thematically and geographically in Europe, while the last one follows Mary’s legacy. Contributors include: Elliott D. Wise, Anna Dlabačová, James Clifton, Kim Butler Wingfield, Barbara Baert, Steven Ostrow, Barbara Haeger, Shelley Perlove, Cristina Cruz González, and Mehreen Chida-Razvi.